We Need Strong Public Health Care to Contain the Global Corona Pandemic - De Ceukelaire, Wim (Int J Health Serv, 2020)
The corona virus (COVID-19) outbreak has spread from China to over a hundred countries in less than 2 months. Now is the time to take stock and to assess the responses of different countries to the outbreak so far. What we can learn from the global Corona pandemic so far is that strong public health systems have the resilience to address massive health threats with the collective responses they require. Privatization of health services and individualization of risks might further undermine our ability to address this and future global pandemics.